Caracterización de la población asistente al centro de atención Psicológico de la Universidad Antonio Nariño. (2023)
The purpose of this research was to characterize the population attending the Psychological Care Center (CAP) of the Antonio Nariño University in the city of Ibagué, which served as a basis for monitoring clinical records in the years analyzed, generating statistical information on the population. attended in reference to the main reasons for consultation and diagnoses, as well as the determination of the social characteristics of the people who demand psychological services. Using the data analysis of records of medical records and consultations made by people between 2 and 78 years of age from the year 2018 to the year 2022-A. It is a non-experimental investigation with a quantitative approach and a cross-section under the empirical-analytical paradigm, without manipulation of variables